PSYCHOLOGICAL CHARACTERISTICS OF BEHAVIOR CONTROL IN ADOLESCENT PERIOD (Web of Teachers: Inderscience Research, 2024)
The article reveals the psychological characteristics of the manifestation of self-control in adolescence. First of all, the analysis of opinions about the content of the concept of self-management, self-management in educational activities is presented. In particular, the levels of manifestation of self-control in behavior during adolescence have been studied on the basis of empirical studies.